Frontotemporal dementia and neurocysticercosis. A case report - Corina Satler (Dementia & Neuropsychologia, 2012)
We report a case of a 67-year-old woman with frontotemporal dementia (FTD) and a history of neurocysticercosis. After her retirement she showed progressive behavioral changes and neuropsychiatric symptoms with relative preservation of cognitive functioning. During the next three years, the patient manifested progressive deterioration of verbal communication gradually evolving to mutism, a hallmark of cases of progressive nonfluent aphasia.